PERMAINAN TRADISONAL DAERAH JAMBI DALAM KARYA SENI PATUNG REALIS - PINO YUDHI WINARA, Dra. Lisa Widiarti, M.Sn., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2018)
The purpose of this final work is to visualize some kind of tradisional Jambi game form in the form of realist style sculpture art, art idea presents children figura as subject matter which illustrates playing tradisional game of Jambi area. Methods in realizing ideas through the preparation, elaboratin, synthesis, concept realization, and exhibition. The sculpture works reminiscent of the tradisional of the region that began to be forgotten among the children in the Jambi area. Seven titles of works that have been made is 1) Main adang-adangan, 2) Main gunung, 3) Main kak lele, 4) Main Gasing, 5) Main Kelereng, 6) Main Egrang, 7) Main Bakiak.Kata kunci : Permainan Tradisional, Jambi, Patung, Realis.